2011
DOI: 10.3109/02688697.2011.591948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrathecal magnesium sulfate solution injection via a microcatheter in the cisterna magna on cerebral vasospasm in the canine subarachnoid haemorrhage model

Abstract: Intracisternal MgSO(4) therapy using a microcatheter from the lumbar spine may be effective against vasospasm in the clinical setting of endovascular treatment of ruptured aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…[5] Neuroprotective effects of magnesium sulfate and its effect on cerebral blood flow[67] can be advantageous during controlled hypotension. However, there are the potential risks of magnesium such as, potentiation of opioids and neuromuscular blockers leading to delayed emergence.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Neuroprotective effects of magnesium sulfate and its effect on cerebral blood flow[67] can be advantageous during controlled hypotension. However, there are the potential risks of magnesium such as, potentiation of opioids and neuromuscular blockers leading to delayed emergence.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental settings, magnesium treatment preserves the ischemia-induced reduction in S-100 proteins, possibly by restoration of blood brain permeability during hypoxia [28] . Additionally, Mori et al [29] have described neuro-protective effects following intrathecal infusion of magnesium in a rat model of subarachnoid hemorrhage. Neuroprotective effects of magnesium are considered advantageous during controlled hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…The various mechanisms of action of Mg 2+ include reduction of excitatory amino acid release, blockage of the NMDA-glutamate receptor and voltage-dependent calcium channels, inhibition of platelet aggregation, inhibition of endothelin-1 synthesis, vasodilation through the release of endothelial nitric oxide (NO), and increased synthesis of prostacyclins (Berthon et al, 2003; Nadler et al, 1987; van den Bergh et al, 2004; Yang et al, 2000). Both animal studies and pilot clinical trials using magnesium sulfate have reported trends toward improved outcomes (Mori et al, 2011, 2012). In the Field Administration of Stroke Therapy–Magnesium (FAST-MAG) pilot trial, prehospital administration of magnesium is feasible and safe in acute ischemia stroke patients (Saver et al, 2004).…”
Section: 3 Neurobiological Response After Sahmentioning
confidence: 99%